Plant Protein O-Arabinosylation - Petersen, Bent Larsen; MacAlister, Cora A.; Ulvskov, Peter (Frontiers in Plant Science, 2021)
A wide range of proteins with diverse functions in development, defense, and stress responses are O-arabinosylated at hydroxyprolines (Hyps) within distinct amino acid motifs of continuous stretches of Hyps, as found in the structural cell wall extensins, or at non-continuous Hyps as, for example, found in small peptide hormones and a variety of plasma membrane proteins involved in signaling. Plant O-glycosylation relies on hydroxylation of Prolines to Hyps in the protein backbone, mediated by prolyl-4-hydroxylase (P4H) which is followed by O-glycosylation of the Hyp C4-OH group by either galactosyltransferases (GalTs) or arabinofuranosyltranferases (ArafTs) yielding either Hyp-galactosylation or Hyp-arabinosylation. A subset of the P4H enzymes with putative preference to hydroxylation of continuous prolines and presumably all ArafT enzymes needed for synthesis of the substituted arabinose chains of one to four arabinose units, have been identified and functionally characterized. Truncated root-hair phenotype is one common denominator of mutants of Hyp formation and Hyp-arabinosylation glycogenes, which act on diverse groups of O-glycosylated proteins, e.g., the small peptide hormones and cell wall extensins. Dissection of different substrate derived effects may not be regularly feasible and thus complicate translation from genotype to phenotype. Recently, lack of proper arabinosylation on arabinosylated proteins has been shown to influence their transport/fate in the secretory pathway, hinting to an additional layer of functionality of O-arabinosylation. Here, we provide an update on the prevalence and types of O-arabinosylated proteins and the enzymatic machinery responsible for their modifications.